Ensuring Member Savings Protection During the Covid-19 Pandemic: A Case Study of KSPPS Istiqlal Pekalongan, Central Java, Indonesia - Moh. Arifin; Noor Rosyidah; Deni Parama Widia Astuti; Afif Noor; Mahsun Mahsun; Ismail Marzuki (Qubahan Academic Journal, 2023)
This study aims to determine the basis for protecting members' savings and the efforts made by KSPPS Istiqlal managers in protecting their members' savings during the COVID-19 pandemic. The method of approach used in this study is empirical-juridical, based on primary and secondary data. Interviews with KSPPS Istiqlal managers provided primary data, while secondary data came in the form of legal documents, both primary documents originating from statutory regulations and secondary legal materials obtained from the literature. According to the findings based on primary and secondary data, property protection is the foundation of legal protection for members of the KSPPS Istiqlal, which is one of the maqashid shariah and the Constitution of 1945. Efforts made by the KSPPS Istiqlal manager to protect members' savings during the COVID-19 pandemic included, among others, maintaining financial liquidity of at least 25%, not channeling all member savings funds in the form of financing, and rescheduling KSPPS Istiqlal members who receive financing and experience difficulties paying their financing installments.